MUSIK TRADISIONAL DAYAK DI ERA DIGITAL: MERETAS REVOLUSI INOVASI REBAB SANGGILING BULAU UNTUK MENINGKATKAN KEBERLANJUTAN KEARIFAN LOKAL DALAM ERA TEKNOLOGI - Samosir, Hendro T. G.; Maulana, Muhammad Ahsin; Asi, Yuliati Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Traditional musical instruments are one of the important elements in preserving local wisdom. In the context of Dayak local wisdom, Rebab Sanggiling Bulau is a traditional musical instrument of the Dayak tribe that has spiritual value and is a symbol of rich and historical cultural identity. However, in the midst of globalization and rapid technological developments, the existence of traditional musical instruments such as Rebab Sanggiling Bulau typical of Dayak has its own challenges in its preservation. The existence of Rebab Sanggiling Bulau is threatened by minimal documentation, lack of regeneration and dominance of popular culture. For this reason, digital technology is needed that can be integrated with creative innovation to promote and expand appreciation of Rebab Sanggiling Bulau. This study aims to examine the potential of digital innovation to maintain cultural values ​​and as a preservation of Rebab Sanggiling Bulau. The research method is qualitative through a literature study approach and descriptive analysis. Data collection techniques use observation, interviews, and FGD (Focus Group Discussion). From the results of organological observations of Sanggiling Bulau, as well as interviews and FGDs with sources and traditional music practitioners, efforts to preserve Rebab Sanggiling Bulau as local wisdom include documentation, so that the technological innovation needed is the digitalization of Rebab Sanggiling Bulau sound with the help of a tool called a spull and a sound effect plugin on DAW (Digital Audio Workstation). The technological innovation carried out on Rebab Sanggiling Bulau is expected to attract the attention of the younger generation, so that the younger generation will learn traditional musical instruments that will have an impact on the preservation of traditional music as a continuation of local wisdom in the digital era.